Cultural dilemmas of motherhood and gendered public/private spheres: The case of a remediatized Chinese reality show. (December 2020) - Lazar, Michelle M.; Sun, Ke
Abstract: This article examines how the gendered dichotomization of spaces continues to operate as a patriarchal technology for the maintenance of hierarchical social orders in the contemporary period. Adopting a Feminist Critical Discourse Analysis (FCDA) perspective, this article considers the extent to which the gendered nei-wai ('inside'/'outside') spatial ideology in China, based on complementarity of gendered roles, prevails in contemporary Chinese society. We focus on motherhood discourses in relation to two contrastive family structures (a single-male-income family and a dual-income family) featured on the popular Chinese reality show Love Battle. Our data are based on a 'remediatisation' of the television show on two Chinese video-sharing websites. By using the remediatised data, we are able to provide a combined analysis of the discourses by the show's participants as well as by their online viewers (via the websites' danmaku feature). The combined analysis provides insight into the uptake of the gendered nei-wai ideology, as evident in the attitudes and practices regarding motherhood in contemporary Chinese society.